2021
DOI: 10.1007/s10811-021-02427-x
|View full text |Cite
|
Sign up to set email alerts
|

Biomass and height of Ascophyllum nodosum after two decades of continuous commercial harvesting in eastern Canada

Abstract: With the increasing demand for seaweed resources worldwide, management must ensure that the harvest of wild seaweed stocks is sustainable. We evaluate the impact of over 25 years of commercial harvesting of Ascophyllum nodosum in eastern Canada by comparing the biomass and height of the seaweed in the late 1990s to the late 2010s over a broad spatial scale spanning the provinces of Nova Scotia and New Brunswick. There has been no significant decrease in the biomass of A. nodosum in either province, and biomass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 52 publications
(69 reference statements)
0
9
0
Order By: Relevance
“…Ascophyllum nodosum is commercially harvested in several countries (mainly Canada, Ireland, Norway, Iceland, USA, Scotland, and France). Regulations vary between countries; for example, the maximum harvest rate in New Brunswick, Canada, is set at 17% of the standing stock (Ugarte and Sharp 2001;Lauzon-Guay et al 2021). According to previous productivity estimates based on the most apical growth segment (Cousens 1984), it was estimated that this harvest rate represented between 15.1 and 18.7% of the annual A. nodosum production in southern New Brunswick (Ugarte et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ascophyllum nodosum is commercially harvested in several countries (mainly Canada, Ireland, Norway, Iceland, USA, Scotland, and France). Regulations vary between countries; for example, the maximum harvest rate in New Brunswick, Canada, is set at 17% of the standing stock (Ugarte and Sharp 2001;Lauzon-Guay et al 2021). According to previous productivity estimates based on the most apical growth segment (Cousens 1984), it was estimated that this harvest rate represented between 15.1 and 18.7% of the annual A. nodosum production in southern New Brunswick (Ugarte et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These yearly air bladders have also been used to calculate yearly growth and productivity estimates for the species (Baardseth 1970;Cousens 1984;Vadas et al 2004). Ascophyllum nodosum is commercially harvested on both sides of the North Atlantic (Mac Monagail et al 2017), and quotas are often determined based on productivity estimates of the species to ensure recovery (Ugarte and Sharp 2001;Lauzon-Guay et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Kelly et al [ 57 ] reported that sites in Ireland at Clew Bay and Connemara demonstrate almost complete recovery of A. nodosum 11- and 17-months post-hand harvesting, respectively. In Canada, 2 to 5 years was suggested for A. nodosum biomass recovery ([ 86 ] and references therein), which was observed within 3 years post-removal of 50% of the biomass ([ 86 , 87 ] and references therein). Rapid recovery may be due to stimulation of growth and branching of the suppressed shoots of the clumps [ 88 ].…”
Section: Resources Sustainability and Regulation Of Seaweed-based Bio...mentioning
confidence: 99%
“…Rapid recovery may be due to stimulation of growth and branching of the suppressed shoots of the clumps [ 88 ]. A. nodosum is harvested in Canada from small boats using a hand-held cutting rake [ 87 ].…”
Section: Resources Sustainability and Regulation Of Seaweed-based Bio...mentioning
confidence: 99%
“…The existence of vast marine areas suitable for seaweed farming makes champions of seaweeds envision a forthcoming "Seaweed Revolution". 5 There is a growing consensus that wild resources will not be able to supply enough seaweeds to satisfy future demand despite the robust management strategies in many areas (Steen et al, 2016;Monagail et al, 2017;Lauzon-Guay et al, 2021). Aquaculture is the primary means to ensure safety and traceability and to help unlock the great potential of seaweeds.…”
Section: Introductionmentioning
confidence: 99%